ANALISIS PENGARUH GAYA HIDUP GEN Z TERHADAP TATA KELOLA KEUANGAN PRIBADINYA - Maulana, Muhamad Chandra; Hatimatunnisani, Hani; Oktapiani, Syarah; Fitria Zaharah, Mela; De Keizer, Hendriady (Jurnal Ekonomi Manajemen Bisnis Dan Akuntansi : EMBA, 2024)
“Gen Z”, or Generation Z was born in late 1997 until 2012. This generation grew up with the internet and digital technology as a thing that distinguishes them from the previous generation. This research aims to analyze how Generation Z’s lifestyle influences personal finance management. Quantitative methods with simple regression and correlation are used in this analysis to measure the statistical relationship between Gen Z lifestyle and personal financial management. A survey of 100 gen z was used as a research sample. The results of the analysis that has been carried out shaw that the Gen Z lifestyle does not have a significant effect on personal financial management. However, positive correlation results show that the positive lifestyle of Gen Z will have a better influence on personal financial management.